2000
DOI: 10.1038/sj.bjp.0703414
|View full text |Cite
|
Sign up to set email alerts
|

The inhibition of cholera toxin‐induced 5‐HT release by the 5‐HT3 receptor antagonist, granisetron, in the rat

Abstract: 1 The secretagogue 5-hydroxytryptamine (5-HT) is implicated in the pathophysiology of cholera. 5-HT released from enterochroman cells after cholera toxin exposure is thought to activate nonneuronally (5-HT 2 dependent) and neuronally (5-HT 3 dependent) mediated water and electrolyte secretion. CT-secretion can be reduced by preventing the release of 5-HT. 2 Enterochroman cells possess numerous receptors that, under basal conditions, modulate 5-HT release. These include basolateral 5-HT 3 receptors, the activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 26 publications
0
37
0
Order By: Relevance
“…The 5-HT 1 , 5-HT 3 , and 5-HT 4 receptor subtypes play major roles in motor, sensory, and secretory function of the GI tract [Gershon, 1999]. Intestinal 5-HT release is associated with smooth muscle contraction, increased luminal secretions, and reduced GI transit time [Turvill et al 2000;Ruckebusch and Bardon, 1984]. The blockade of 5HT 3 receptors, notably by antiemetics such as ondansetron, has been observed to result in constipation [Haus et al 2004].…”
Section: Antidepressantsmentioning
confidence: 99%
“…The 5-HT 1 , 5-HT 3 , and 5-HT 4 receptor subtypes play major roles in motor, sensory, and secretory function of the GI tract [Gershon, 1999]. Intestinal 5-HT release is associated with smooth muscle contraction, increased luminal secretions, and reduced GI transit time [Turvill et al 2000;Ruckebusch and Bardon, 1984]. The blockade of 5HT 3 receptors, notably by antiemetics such as ondansetron, has been observed to result in constipation [Haus et al 2004].…”
Section: Antidepressantsmentioning
confidence: 99%
“…One mechanism, for which the evidence is very strong, is concomitant activation of the enteric nervous system. Enteric nervous components directly or indirectly involved with CT's actions are serotonin (5-HT) released from enterochromaffin cells (48), activation of 5-HT 3 receptors (3,4,34,49), activation of intrinsic primary afferent neurons (10), involvement of nicotinic interneurons (6,19), and a contribution of secretomotor neurons releasing vasoactive intestinal peptide (VIP) (5,33). These different components have been well documented in vivo, but the exact neurophysiological mechanisms are not well defined, because there is no good in vitro model as yet.…”
mentioning
confidence: 99%
“…66,67 Serotonin release from enterochromaffin epithelial cells is stimulated by tryptamine 83 and is a key regulator of the gut motility and secretion. 84 Recently, it has been shown that gut microbiota, acting through SCFAs, is an important determinant of enteric serotonin production and homeostasis. The gut microbiota from ex-GF mice colonized with human gut microbiota and conventionally raised mice the colonic rate limiting for mucosal serotonin synthesis; tryptophan hydroxylase 1 mRNAs as well as the neuroendocrine secretion gene; chromogranin A with no effect on the serotonin transporter or serotonin catabolic gene; monoamine oxidase A.…”
mentioning
confidence: 99%